Marketing strategies of economic entities (on the example of persons carrying out activities in the field of customs business) - S. V. Kurikhin (Вестник университета)
The subject of the research is the marketing strategy of persons carrying out activities in the field of customs. The purpose of the article is to develop proposals for improving the marketing strategy of customs representatives. The author used the following scientific methods: analysis and synthesis, comparison, induction and deduction. In the course of the study, the application of the theoretical design of the marketing complex 5P for the analysis of marketing strategies of participants in foreign economic activity was studied; the marketing strategies of customs representatives were compared; shortcomings of marketing strategies were identified and proposals for their improvement were developed. The scope of the results is primarily within the interests of marketing practitioners and scientists, since this specific area has not been practically studied. In addition, the results can be useful in the educational process, when teaching such disciplines as Marketing and Economic security of an enterprise participating in foreign economic activity. Based on the material presented in the article, it was concluded that the inactive marketing activities of the majority of customs representatives may lead to the termination of their activities in the face of growing competition in the market.